2005
DOI: 10.1111/j.1365-2044.2005.04298.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remifentanil with and without atropine on heart rate variability and RR interval in children

Abstract: SummaryRemifentanil can cause bradycardia either by parasympathetic activation or by other negative chronotropic effects. The high frequency (HF) component of heart rate variability (HRV) is a marker of parasympathetic activity. This study aimed to evaluate the effect of remifentanil on RR interval and on HRV in children. Forty children ASA I or II were studied after approval by the human studies committee and informed parental consent was obtained. After stabilisation at sevoflurane 1 MAC, they were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 25 publications
(30 reference statements)
3
31
1
1
Order By: Relevance
“…This may indicate that lowdose remifentanil induces parasympathetic nerve activation without adverse hemodynamic or respiratory effects. This is partly inconsistent with previous reports, where remifentanil did not trigger the activation of the parasympathetic nervous system (5)(6)(7)(8). This difference may be partly attributable to the clinical presentation and demographics of the patients studied; the subjects for the study by Tirel et al (5) were children whereas our study subjects were adults.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This may indicate that lowdose remifentanil induces parasympathetic nerve activation without adverse hemodynamic or respiratory effects. This is partly inconsistent with previous reports, where remifentanil did not trigger the activation of the parasympathetic nervous system (5)(6)(7)(8). This difference may be partly attributable to the clinical presentation and demographics of the patients studied; the subjects for the study by Tirel et al (5) were children whereas our study subjects were adults.…”
Section: Discussioncontrasting
confidence: 56%
“…Fujiwara et al (3) showed that spinal anaesthesia induced a decrease of both sympathetic and parasympathetic nerve activities. Several reports describe the effects of opioids on the activity of the sympathetic or parasympathetic nervous system (4)(5)(6)(7)(8). Carter et al (4) examined the effects of morphine on sympathetic nerve activity in humans and found that the intravenous injection of morphine increased sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence suggests that the rate of recovery after remifentanil in neonates less than 1 week old may be greater than it is in infants 7 days to 3 months of age [ 256 ]. Pharmacodynamically, remifentanil may induce bradycardia, an effect classically attributed to the parasympathomimetic properties of remifentanil, a direct negative chronotropic effect [ 257 ]. The decrease in heart rate attributable to remifentanil after 5 μg/ kg was infused over 1 min, peaks at 3 and 5 min after the infusion, but was less impressive in infants ≤2 months than in older children, although only 8 infants ≤2 months were included [ 258 ].…”
Section: Analgesiamentioning
confidence: 94%